2023
DOI: 10.1186/s12935-023-02916-8
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer-derived small extracellular vesicles induce TGFβ1-mediated epithelial to mesenchymal transition of hepatocytes

Abstract: Background Metastatic disease is the major cause of cancer-related deaths. Increasing evidence shows that primary tumor cells can promote metastasis by preparing the local microenvironment of distant organs, inducing the formation of the so-called “pre-metastatic niche”. In recent years, several studies have highlighted that among the tumor-derived molecular components active in pre-metastatic niche formation, small extracellular vesicles (sEVs) play a crucial role. Regarding liver metastasis, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Small extracellular vesicles derived from colorectal cancer (CRC) cells directly target hepatocytes, trigger epithelial‐mesenchymal transition (EMT) and form a fibrotic microenvironment 13 . Yoong et al demonstrated that CRC metastatic cells induced the expression of Factor‐related Apoptosis (Fas) in hepatocytes, killing them by cytotoxic T lymphocytes (CTL) or tumor cells carrying Factor‐related Apoptosis ligand (FasL), and promoting local invasion of cancer cells 14 .…”
Section: Hepatic Parenchymal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small extracellular vesicles derived from colorectal cancer (CRC) cells directly target hepatocytes, trigger epithelial‐mesenchymal transition (EMT) and form a fibrotic microenvironment 13 . Yoong et al demonstrated that CRC metastatic cells induced the expression of Factor‐related Apoptosis (Fas) in hepatocytes, killing them by cytotoxic T lymphocytes (CTL) or tumor cells carrying Factor‐related Apoptosis ligand (FasL), and promoting local invasion of cancer cells 14 .…”
Section: Hepatic Parenchymal Cellsmentioning
confidence: 99%
“…In the process of liver metastasis of CRC cells, cells in the liver microenvironment are mobilized to play different roles. Pucci's et al study shows that CRC extracellular vesicles carrying TGF‐β1 damage hepatocytes by triggering TGFβ1/SMAD‐dependent EMT 13 . Wei et al demonstrated that TAMs enhanced CRC migration and invasion by regulating JAK2/STAT3/miR‐506‐3p/FoxQ1 axis to induce EMT 59 .…”
Section: Liver Metastasis Of Different Tumorsmentioning
confidence: 99%
“…Abundant signaling pathways (including Wnt, TGF-β, p53, mTOR, MAPK, and JAK-STAT) and multiple transcriptional factors (such as TWIST, SNAIL, Slug, FOX, and zinc-finger E-box binding (ZEB)) have been described to modulate EMT. EVs derived from diverse cells in CRC microenvironment have been implicated in initiating metastasis and driving EMT [ 34 36 ].…”
Section: Role Of Sevs In Crc Progression and Metastasismentioning
confidence: 99%